Thermodynamic reasons of agglomeration of dust particles in the thermal dusty plasma - Vishnyakov, V.I.; Dragan, G.S. (Condensed Matter Physics, 2003)
The thermodynamic equilibrium of thermal dusty plasmas consisting of ionized gas (plasma) and solid particles (dust grains), which interact with each other, is studied. The tendency of grains in dusty plasmas to agglomerate corresponds to the tendency of dusty plasmas to balanced states. When grains agglomerate, electrical perturbations generated by each grain concentrate inside the agglomerate. The plasma is perturbed only by the agglomerate’s exterior surface. The greater number of possible states for electrons and ions in plasma depends on the volume of perturbation of grains. The fewer are the perturbations the greater is the amount of possible states for electrons and ions in plasma. If the grains collected from a distance smaller than 8 Debye lengths, the total volume of perturbations is minimized; the free energy of the plasma is also minimized.